Game on! A state-of-the-art overview of doing business with gamification - Sharma, Wamika; Lim, Weng Marc *; Kumar, Satish *; Verma, Aastha; Kumra, Rajeev (Elsevier, 2024)
Gamification is the act of applying game-design elements to transform activities, products, services, and systems in a way that provides the kind of experiences similar to those offered by games. These elements include badges, points, and leaderboards to motivate and reward problem solving activities and processes. Both businesses and business researchers are increasingly interested in the application of gamification. In this regard, this review aims to offer a state-of-the-art overview of gamification in business, revealing its current trends and future directions. Using business research on gamification published in the last decade (2012–2022) found on Scopus and Web of Science, we conduct a performance analysis to illuminate the field's performance (publication productivity and impact) alongside its key contributors (journals, authors, and countries) as well as a science mapping using a co-citation analysis to locate knowledge foundations, and bibliographic coupling and keyword co-occurrence analysis to reveal major themes in business gamification. Our exploration has unearthed gamification's pervasive influence across business domains, from enhancing learning and fostering innovation to empowering marketing strategies and catalyzing transformation. Gamification has also made significant inroads into management practices, driving engagement, influencing behavioral outcomes, and ushering sustainability. Peering into the future, our density-centrality quadrant analysis casts light on emerging frontiers. Noteworthily, we expect the next wave of gamification to be shaped by the allure of video games and the metaverse, bespoke industry-specific designs, confluence with e-commerce trends, emphasis on sustainable development, expanded social responsibilities, innovations in virtual reality, intersections with human urbanism, and the rise of smart cities. As gamification continues to integrate and reshape myriad facets of the business world, it holds the promise of not only enriching current practices but also charting the course for the future of innovative, sustainable, and transformative business strategies.